Detection of latent tuberculosis infection in BCG vaccinated children - Maciejewska, Barbara; Milanowski, Janusz (Polish Journal of Public Health, 2011)
Asthma and chronic obstructive pulmonary disease (COPD) are often confused with each other, and also primary care physicians too often outsource spirometry to diagnose a patient with shortness of breath. Poorly placed diagnosis results in wrong treatment, and this may result in adverse consequences for the patient. With proper tests it is possible to detect both restrictive and obstructive lung disease, even in the early stages. Test is recommended in cases of: smoking, exposure to noxious fumes and dust, long lasting cough, shortness of breath with both exertion and rest. Around the world, 100-150 million people suffer from asthma. WHO Bronchial Asthma Fact Sheet 2000 indicates that every ten years, the global incidence rate increased by 50%. The costs of asthma are higher compared to the HIV/AIDS and tuberculosis. The dominant cause of severe acute asthma (according to the GINA Guidelines) is misdiagnosis and inappropriate treatment. The objective diagnostic parameters evaluated in spirometry include: forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF), which always require individual interpretation. The percentage of proper of the spirometric tests, in some centers did not exceed 15%. If the test was not performed properly it is impossible to correctly interpret the result. Each of the steps should be executed flawlessly. Only a properly constructed and well-interpreted spirometry is useful in diagnosis and treatment of asthma.